Cardiac metabolism in HFpEF: from fuel to signalling. Issue 18 (12th December 2022) - Capone, Federico; Sotomayor-Flores, Cristian; Bode, David; Wang, Rongling; Rodolico, Daniele; Strocchi, Stefano; Schiattarella, Gabriele G
Abstract: Heart failure (HF) is marked by distinctive changes in myocardial uptake and utilization of energy substrates. Among the different types of HF, HF with preserved ejection fraction (HFpEF) is a highly prevalent, complex, and heterogeneous condition for which metabolic derangements seem to dictate disease progression. Changes in intermediate metabolism in cardiometabolic HFpEF—among the most prevalent forms of HFpEF—have a large impact both on energy provision and on a number of signalling pathways in the heart. This dual, metabolic vs. signalling, role is played in particular by long-chain fatty acids (LCFAs) and short-chain carbon sources [namely, short-chain fatty acids (SCFAs) and ketone bodies (KBs)]. LCFAs are key fuels for the heart, but their excess can be harmful, as in the case of toxic accumulation of lipid by-products (i.e. lipotoxicity). SCFAs and KBs have been proposed as a potential major, alternative source of energy in HFpEF. At the same time, both LCFAs and short-chain carbon sources are substrate for protein post-translational modifications and other forms of direct and indirect signalling of pivotal importance in HFpEF pathogenesis. An in-depth molecular understanding of the biological functions of energy substrates and their signalling role will be instrumental in the development of novel therapeutic approaches to HFpEF. Here, we summarize the current evidence on changes in energy metabolism in HFpEF, discuss the signalling role of intermediate metabolites through, at least in part, their fate as substrates for post-translational modifications, and highlight clinical and translational challenges around metabolic therapy in HFpEF.